EFFECTIVENESS OF ENDHORPHIN MASSAGE AND EFFLEURAGE MASSAGE WITH LAVENDER AROMATHERAPY ON MENSTRUAL PAIN SCALE OF ADOLESCENT FEMALES IN THE WORKING AREA OF KARANGDORO COMMUNITY HEALTH CENTRE - Vita, Vita Triani Adi Puteri; Wijayanti, Heni; Jaya Rochkmana, Meika; Candrawuni Fatona, Riska (Jurnal Smart Kebidanan, 2025)
Menstruation is a condition in which a woman experiences pain during menstruation and has a bad effect that causes disruption in carrying out daily activities. This condition can occur for 3 days or more each menstruation. One of the non-pharmacological treatments that can be given for example is Endorphin massage and Effleurage massage. Based on the research journal of Razmjooee and Maria Elvira, both of these treatments are very effective in reducing pain because they both function to produce endorphin hormones. The research design used in this study was a quasi-experimental study with a pretest-post test with two group design. The Wilcoxon test showed that there was a difference in the effectiveness of Endorphin Massage with Lavender Aromatherapy and Effleurage Massage with Lavender Aromatherapy on the intensity of dysmenorrhea pain in adolescent girls, while the Mann Whitney test showed that there was no difference in the effectiveness of Endorphin Massage with Lavender Aromatherapy and Effleurage Massage with Lavender Aromatherapy on the Scale of Menstrual Pain in Adolescent Girls in the Karangdoro Health Center Work Area, Semarang City.It is hoped that the results of this study will be useful for reducing menstrual pain in adolescent girls.